The Indian Mutual Fund Industry: From Inception to Advancement - Yadav, Ajay Pratap (Indian Journal of Finance, 2015)
Inception of the Indian mutual fund industry was a consequence of progressive liberalization that brought about dramatic changes in the Indian financial system. Liberalization of economic policies caused rapid growth of the capital market, money market, and financial services industry. The Indian mutual fund industry is one of the major results of financial novelty in the Indian context. However, its popularity as an investment option is still debatable. The study was concerned with the journey of the Indian mutual fund industry since its beginning in India. To serve the purpose, the study focused on the following areas : historical perspectives of the Indian mutual fund segment, growth aspect of the mutual fund industry, and the last section highlighted major challenges, issues, and growth prospects of the Indian mutual fund industry.